A Reconstruction of a Creation of a Transcribed Text on a Basis of Its Content and Linguistic Features - Andrić, Marta (Prilozi za orijentalnu filologiju, 2017)
A manuscript legacy in Turkish by a priest Gjuro Adam Büttner (1714-1779) was created in Zemun in 18th century and it is kept in the Central Archiepiscopal and Faculty Library in Đakovo. It consists of a German-Turkish dictionary and the accompanying material of three leaflets and four fascicules with catechism and philological content. This paper is dedicated to these additional sources through which we can – up to a certain point – reconstruct ways and sources from which Büttner learnt Turkish. In that way the process of dictionary compilation can be reconstructed as well – and the dictionary is the greatest part of the legacy. Through analysis, it was established that Büttner knew grammars and dictionaries of Turkish language by Holdermann, Meninski and Molino. The comparison of the language of the accompanying material shows that there is a direct connection between them. Also, the texts in the fascicules could partly be considered as a preparatory work for dictionary, which further means that Büttner’s dictionary could be considered author’s work. The features of the Western Rumeli Turkish that are present in Büttner’s language, although sparsely, probably stem from literature used, while the closeness of his language to the language that was used in Istanbul approximately in his time, could be explained for now only by a possible living language contact.